2022
DOI: 10.1017/s0950268822001844
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 isolation/quarantine rules in home care patients

Abstract: The spread of SARS-CoV2 new variants increased the number of subjects in home isolation and quarantine. The aim of this study was to assess the compliance with COVID-19 home isolation rules for 32 subjects in home care in Marche Region, Italy. The results showed that subjects in home isolation were better informed about isolation rules (p=0.007) than those who were in quarantine. They had lower educational level (p <0.001) and none/single income (p <0.001) and higher rate of clinical manifestation.The educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[41] One study reported two prevalence estimates. [76] Twenty prevalence estimates were at very high risk of bias, [21, 23, 24, 28, 29, 3137, 40, 47, 6972, 74, 76–78] 14 were at high risk, [21, 22, 27, 38, 4446, 73, 79, 8183, 85] ten had some concerns, [25, 26, 30, 39, 42, 43, 48–68, 80, 84] and one was at low risk. [75] Full details for each study are reported in Supplement S6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[41] One study reported two prevalence estimates. [76] Twenty prevalence estimates were at very high risk of bias, [21, 23, 24, 28, 29, 3137, 40, 47, 6972, 74, 76–78] 14 were at high risk, [21, 22, 27, 38, 4446, 73, 79, 8183, 85] ten had some concerns, [25, 26, 30, 39, 42, 43, 48–68, 80, 84] and one was at low risk. [75] Full details for each study are reported in Supplement S6.…”
Section: Resultsmentioning
confidence: 99%
“…[23, 29, 30, 34–43, 45–68, 73, 75–78, 8183] Of these, 24 were assessed using the ROBINS-E. Analyses of associations from seven studies were at very high risk of bias, [30, 34, 37, 38, 73, 77, 78, 83], 15 were at high risk of bias, [23, 29, 35, 36, 40–43, 47–68, 75, 76, 81, 82] and two had some concerns (Supplement S6). [39, 45] One study was assessed using the ROBINS-I and was rated as very high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation